2010
DOI: 10.1590/s0101-28002010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Terapia de indução com alentuzumabe em receptores de transplante renal

Abstract: Introduction: Induction therapy has been used in sensitized patients, re-transplants, and in patients who have high risk to delayed graft function (DGF) after renal transplantation. Methods: Retrospective study with aim to compare transplant endpoints between recipients of deceased donors which have received induction with alemtuzumab (n = 9) versus thymoglobulin (n = 18). Patients were matched for age, duration of dialysis treatment and cold ischemia time. Results: There were no differences at demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…These outcomes are consistent with recent studies. [34][35][36] Other authors have shown that ECD kidneys had worse long-term graft function and survival outcomes. 3,37 However, they provide acceptable function and significantly better patient survival when compared to dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are consistent with recent studies. [34][35][36] Other authors have shown that ECD kidneys had worse long-term graft function and survival outcomes. 3,37 However, they provide acceptable function and significantly better patient survival when compared to dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Basiliximabe apresentou a mesma eficácia que o policlonal globulina anti-timocítica equina (ATG) e o inibidor de IL-2 Daclizumabem estudos, porém apresentou-se mais eficaz que o Muromonabe CD3, mostrando-se capaz de dispensar o uso de corticosteroides na terapia. 16 Em uso livre, não apresenta efeitos colaterais significativos, comparado com os imunossupressores convencionais. Porém, podem ocorrer alguns problemas gastrointestinais, dor abdominal, vômito, pressão baixa, dor de cabeça, tonturas, insônia, formigamentos, hiperglicemia, entre outros.…”
Section: • Basiliximabeunclassified